The handbook of humanistic psychology : theory, research, and practice - Schneider, Kirk J.; Pierson, J. Fraser; Bugental, James F. T. (Thousand Oaks, California : SAGE Publications, 2015)
'The Handbook of Humanistic Psychology' addresses the latest scholarship in the resurgent field of humanistic psychology and psychotherapy. The contributors reject many trends leading to a standardised and medicalised approach to the subject.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: Humanistic psychology